2019
DOI: 10.3390/ijms20235960
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass Applications in Dentistry

Abstract: At present, researchers in the field of biomaterials are focusing on the oral hard and soft tissue engineering with bioactive ingredients by activating body immune cells or different proteins of the body. By doing this natural ground substance, tissue component and long-lasting tissues grow. One of the current biomaterials is known as bioactive glass (BAG). The bioactive properties make BAG applicable to several clinical applications involving the regeneration of hard tissues in medicine and dentistry. In dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(147 citation statements)
references
References 195 publications
(226 reference statements)
2
137
0
8
Order By: Relevance
“…Similarly, bioactive glass (BAG), especially Bioglass 45S5 and S53P4, are efficient antimicrobial agents, and their properties make BAG perhaps the ideal bone substitute for treating peri-implant infections. 50…”
Section: Antibiotics and Antimicrobial Agentsmentioning
confidence: 99%
“…Similarly, bioactive glass (BAG), especially Bioglass 45S5 and S53P4, are efficient antimicrobial agents, and their properties make BAG perhaps the ideal bone substitute for treating peri-implant infections. 50…”
Section: Antibiotics and Antimicrobial Agentsmentioning
confidence: 99%
“…Due to this remineralizing property, BAG NPs are incorporated into toothpaste to treat dentine hypersensitivity [286][287][288][289]. In vitro studies have demonstrated that BAG NPs could promote mineral formation on dentin surfaces and they were shown to make dentin more acid-resistant [290,291].…”
Section: Bioactive Glassmentioning
confidence: 99%
“…At present, the most common applications of bioactive glasses in the form of inorganic silica-based melt-derived compositions are based on particulates mainly as bone graft substitute in dentistry and orthopedics [7][8][9][10]. Thus, the first commercially developed 45S5 Bioglass particulate (particle size 90-710 µm) under the trade name of PerioGlas was applied for repairing interproximal bone defects in dentistry [9][10][11][12]. NovaBone is another trade name of 45S5 Bioglass particulate used in bone and tissue regeneration for over 20 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the latest evolution of bone graft material NovaBone Dental Putty appeared on the market in the form of a pre-mixed composite of 45S5 Bioglass particulate and a synthetic, absorbable binder that requires no special mixing procedures prior to use [1]. This new bone replacement product allowed meeting the important requirement of easy handling since normally surgeons tended to mix glass particles with blood from the patient to get putty-like composition which was pressed into the osseous defect [6,9,12].…”
Section: Introductionmentioning
confidence: 99%